1983
DOI: 10.1128/iai.39.2.726-735.1983
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Natural Resistance to Influenza Virus in Lipopolysaccharide-Responsive and -Nonresponsive Mice by Propionibacterium acnes

Abstract: Lipopolysaccharide-responsive C3H/HeN mice were rendered resistant to a mouse-adapted strain of influenza (Aichi, H 3 N 2 ) virus when Propionibacterium acnes was given either intranasally or intraperitoneally several days before virus infection. The time of P. acnes treatment was important since no protection was demonstrated when this agent was given either on the same day as or several days after virus challenge.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…It has been reported that mice administrated with P. acnes enhanced the resistance to influenza virus (Gangemi et al, 1983) and tumor formation (Murano and Cummins, 1989;Mussalem et al, 2006) as well as augmented phagocytic activities (Webster et al, 1979(Webster et al, , 1981aGangemi et al, 1983). These data implied that inactivated P. acnes vaccines may increase host immunity.…”
Section: Discussionmentioning
confidence: 84%
“…It has been reported that mice administrated with P. acnes enhanced the resistance to influenza virus (Gangemi et al, 1983) and tumor formation (Murano and Cummins, 1989;Mussalem et al, 2006) as well as augmented phagocytic activities (Webster et al, 1979(Webster et al, , 1981aGangemi et al, 1983). These data implied that inactivated P. acnes vaccines may increase host immunity.…”
Section: Discussionmentioning
confidence: 84%
“…One nism acts in isolation. Considering that FIV used can: (a) enhance the activities of pulmonary NK cells (Table I); (b) increase the H,02 secretion of macrophages [Arora and Houde, 19921 and PMNL (Table I); (c) initiate the early resistance that declines with time; and (d) other microbial products with similar properties have been shown to provide the nonspecific protection against experimental infection [Glasgow et al, 1977;Spencer et, al., 1977;Gangemi et al, 1983;Mak et al, 19831 it is plausible that the viral preparations stimulated the first line of defense of natural resistance mechanisms to impede the progress of infection in mice so that other immune mechanisms could be developed.…”
Section: Discussionmentioning
confidence: 99%
“…The non-specific activation of macrophages (APCs) and the enhancement of cytokine production by CT cause the subsequent enhance- ment of the adaptive immune responses against influenza viruses, which results in complete protection against infection. Similarly, pretreatment of mice with Propionibacterium acnes (Corynebacterium parvum) or baculovirus before a lethal viral challenge results in lower lung-viral titers and lower mortality (20)(21)(22). In these cases, various constituents of the pathogens used for the pretreatment can activate macrophages and dendritic cells (DCs) via members of the Toll-like receptor (TLR) family on these cells to induce protection against infection (23)(24)(25).…”
Section: -2 Enhancement Of Innate Immunitymentioning
confidence: 99%